The Dissemination and Use of Recorded Scientific Information - Martin, Miles W.; Ackoff, Russell L. (Management Science, 1963)
Two separate field studies of chemists and physicists were made which were concerned with how scientists spend their time, especially the amount and kind of communication in which they engage. Approximately 2,200 chemists and physicists were observed. The studies were also concerned with finding out what journals scientists read, what parts of journals, the purposes for which they are read, and the variance of costs of disseminating information through journals, as well as the effect which characteristics of employing organizations have on the way a scientist spends his time. Outstanding features of the research design and those results which are most likely to be of general scientific interest are presented in this article.